Associations between environmental exposures and asthma control and exacerbations in young children: a systematic review. Issue 2 (12th February 2014) - Dick, Smita; Doust, Emma; Cowie, Hilary; Ayres, Jon G; Turner, Steve
Abstract : Objective: To complete a systematic review of the literature describing associations between all environmental exposures and asthma symptoms and exacerbations in children up to mean age of 9 years. Design: Systematic review. Setting: Reference lists of identified studies and reviews were searched for all articles published until November 2013 in electronic databases (MEDLINE, EMBASE, CINAHL, Cochrane Controls Trials Register). Participants: Studies were selected which examined a link between exposure to environmental factors and asthma symptoms and exacerbations where the study participants were children with a mean age of ⩽9 years. Primary and secondary outcome measures: Indices of asthma symptoms, control and exacerbations. Results: A total of 27 studies were identified including eight where inhaled allergens and four where environmental tobacco smoke (ETS) were the exposures of interest. There was evidence that exposure to allergen, ETS, poor air quality and unflued heaters had a modest magnitude of effect (ORs between 2 and 3). There was also evidence of interactions observed between exposures such as allergen and ETS. Conclusions: Exposure to inhaled allergens, ETS, unflued heaters and poor air quality has an important effect on exacerbations in young children with asthma and should be minimised or, ideally, avoided. Better understanding of the effect of exposure to damp housing, air conditioning and dietary factors plus interactions between environmental exposures associated with exacerbations is required.